PERLINDUNGAN KONSUMEN MENURUT PERATURAN OTORITAS JASA KEUANGAN NOMOR I/POJK.07/2013 - Muhammad Rizki Syafaat (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The Authority of the Financial Services Authority in Providing Legal Protection to Consumers Based on Financial Services Authority Regulation Number I / Pojk.07 / 2013 Concerning Consumer Protection in the Financial Services Sector, namely the authority of the OJK regulates the service and settlement of consumer complaints against financial service businesses. If between the consumer and the financial services business do not reach an agreement to settle the complaint, the consumer can settle the dispute outside the court through an alternative dispute resolution agency determined by the OJK to realize a financial system that grows sustainably and is stable and is able to protect the interests of consumers and the public. Keyword: Consumer Protection.